Investigation and characterization of cross ventilating flows through openings in a school classroom - Chanawat Nitatwichit (2018)
Most Thai state schools use cross flow natural ventilation as a passive cooling system. Information on how window openings are able to provide good ventilation and comfort simultaneously is of great importance. The aim of this study is to investigate cross ventilating flows through the openings of a typical Thai state school classroom. Computational fluid dynamics technique was used as a tool in this simulation. The opening discharge coefficients of six different type windows and a door were determined. Wind, stack and combined effects through the openings were characterized and compared for a range of different wind speeds and surface wall temperatures. Results showed that sliding windows gave the highest Cdvalue among openings considered by stack effect. Casement and side hung (90°) windows appeared to provide high air exchange rates. Their discharge coefficients ranged between 0.63 and 0.83. As far as combined effects are concerned, buoyancy was found to be significant at low wind speed (0.25 m/s). Acceptable indoor airflow patterns and thermal distributions can be expected in the occupied zone. The findings from this investigation are useful to develop a plan for a natural ventilation strategy of classrooms to enhance thermal comfort levels. © 2008, Taylor & Francis Group, LLC.